Self-medication and the advisory role of pharmacists in Riyadh, Saudi Arabia - Amal K Suleiman (Archives of Global Professionals, 2013)
Background: Self-medication with over-the-counter (OTC) remedies is a common practice in both developed and developing countries; however, inappropriate self-medication can have adverse effects and may contribute to the emergence of drug-resistant pathogens. A consultation with pharmacists plays a crucial role in providing efficient professional guidance advice for appropriate use of OTC medicines. Aims: This paper investigated the situations in which patients ask a pharmacist for advice and the factors that affect the patients' decisions for asking advice from a pharmacist in Riyadh, Saudi Arabia. Materials and Methods: A pre-tested structured questionnaire was administered to a sample of 680 patients on a voluntary basis who purchased OTC medicines at various five private pharmacies located in different areas of Riyadh, Saudi Arabia. Patients were asked to answer a set of closed-ended questionnaire about their practice regarding the purchase of medicines and the factors that influence their decisions to ask for consultation from pharmacists. Nonparametric statistical software (STATISTICA 12.0) was used to analyze the data. Results and Conclusions: The overall response rate was 78.9%. The majority of participants 67.2% were found to visit the pharmacy specifically to purchase OTC medication. Surprisingly, only 12.9% were asked the pharmacist for advice. According to the participants, the reasons that did not encourage them to ask advice from pharmacists were found - 58.2% felt shy and reluctant, 32.9% lack of confidentiality, 25.3% the pharmacist is impatient, 22.7% queues inside the pharmacy, and 14.2% did not trust the pharmacists. The current study revealed that the majority of patients tend to self-medicate and did not ask the pharmacist for advice when they purchased OTC medicines. Effort should be made to raise public awareness with regards to the advisory role of pharmacists and discrete facilities should be provided that encourage patients to ask for advice from the pharmacist.